Increased cardiac stiffness is associated with autonomic dysfunction in patients with temporal lobe epilepsy. (26th April 2018) - Fialho, Guilherme L.; Wolf, Peter; Walz, Roger; Lin, Katia
Summary: Autonomic dysfunction is linked to sudden death regardless of the presence of structural heart disease. The pathway from autonomic dysfunction to sudden death is not fully understood, but myocardial sympathetic stimulation leading to arrhythmia and/or cardiac fibrosis might play a role. Our goal was to evaluate cardiac stiffness by echocardiography and its association with clinical, structural, and autonomic variables in people with epilepsy (PWE) compared to healthy controls. A 12‐lead electrocardiogram, treadmill testing, and transthoracic echocardiography from 30 patients with temporal lobe epilepsy (TLE) without any known cardiovascular disorders were compared to 30 individuals without epilepsy matched by sex, age, and body mass index. Distribution of cardiovascular risk factors was similar in both groups. PWE had a higher left ventricle stiffness, left ventricle filling pressure, and greater left atrial volume as well as markers of autonomic dysfunction such as impaired chronotropic index and percentage achieved of predicted peak heart rate at effort. In multiple regressions, autonomic dysfunction explained 52% of stiffness and carbamazepine treatment and polytherapy with antiepileptic drugs (AEDs) explained, additionally, 6% each. Stiffness is increased in young patients with TLE and is related to autonomic dysfunction and to a lesser extent, carbamazepine use and polytherapy with AEDs.